Market, Network, Hierarchy: Emerging Mechanisms of Governance in Business Process Management - Niehaves, Björn; Plattfaut, Ralf (10th IFIP WG 8.5 International Conference on E-Government (EGOV 2011), 2011)
Both financial pressure and customer and service-quality orientation force governments to “innovate their processes.” With governmental processes affecting a large variety of stakeholders both inside and outside the government sector, involving these stakeholders in process innovation becomes an important means of increasing know-how, capacity, and ultimately ensure the legitimacy and acceptance of reform efforts. We contribute to the study of collaborative process innovation by applying a governance theory perspective, in order to understand the factors that impact on collaboration. Our quantitative study of 357 local governments reveals that, with an increasing maturity in process innovation, all types of collaboration (market, network, hierarchy) are increasing in importance. Moreover, we find that, under financial stress, governments tend to involve network partners (e.g. other local governments) in process innovation, while a lack of process management knowledge leads to market-oriented collaboration with consultants. We derive implications for management practice and discuss how the study enhances our understanding of process innovation and collaboration in the public sector.